OS FATORES DE RISCO COMPORTAMENTAIS PARA AS DOENÇAS NÃO TRANSMISSÍVEIS ESTÃO ASSOCIADOS COM A CÁRIE EM ADOLESCENTES - MONTEIRO, Edna Luisa Oliveira (2021)
The adolescence is the second life cicle of oportunities in human life for the prevention of noncommunicable diseases (NCD), because in this period many risk behaviors settle or consolidate, putting the health of adults and elderly at risk. Dental caries is the most prevalent NCD worldwide, and it has been associated with other NCDs of higher mortality, such as asthma in young people, and with cardiovascular diseases and type 2 diabetes in adulthood. The association between caries and these NCDs may be explained by the fact that they share behavior risk factors implicated with an unhealthy lifestyle. Because of the complexity of these associations, the present study used Structural Equation Modeling (SEM) to analyze the association between behavior risk factors (unhealthy diet, tabagism and harmful use of alcohol) and dental caries. The sample was adolescents (18-19 yo) from the second follow-up (2016) of the RPS (Ribeirão Preto, Pelotas and São Luís) consort, in São Luis-MA city. The main exposures evaluated were the latent variables Unhealthy Diet Pattern (sugars, fast-food and salty snacks) and Addictive Behaviors (tabagism and risk of alcohol dependence). The D component of the DMFT index was the outcome of interest in this study. Dental biofilm found was analyzed as a mediator of the association between exposures and outcome. The Socioeconomic Status considered a distal determinant, exerted effects on the other variables of the model (exposures and outcome), being analyzed as a latent variable (head of housedold education, adolescent education, economic class and monthly familiy income). Consistency analysis was also tested for the carie outcome, considering all components of DMFT index. Data were analyzed by SEM, using the Mplus 7.0 software. Unhealthy Diet Pattern was directly associated with caries severity (number of decayed teeth) (CP=0.074, p=0.003), being also mediated by dental biofilm (CP=0.018, p=0.001). Addictive Behaviors were associated with dental caries only by the indirect pathway, mediated by dental biofilm (CP=0.018, p=0.014). Unhealthy Diet Pattern and Addictive Behaviors were correlated with each other between the adolescents (CP=0.198, p <0.001), characterizing the adoption of an unhealthy lifestyle. Public policies for the prevention and control of dental caries must be integrated to the prevention of other NCDs of higher mortality in the future, targeting the common risk factors.